Optical Access to Arteriovenous Cerebral Microcirculation Through a Transparent Cranial Implant. Issue 10 (24th June 2019) - Davoodzadeh, Nami; Cano‐Velázquez, Mildred S.; Halaney, David L.; Jonak, Carrie R.; Binder, Devin K.; Aguilar, Guillermo
Abstract : Background and Objective: Microcirculation plays a critical role in physiologic processes and several disease states. Laser speckle imaging (LSI) is a full‐field, real‐time imaging technique capable of mapping microvessel networks and providing relative flow velocity within the vessels. In this study, we demonstrate that LSI combine with multispectral reflectance imaging (MSRI), which allows for distinction between veins and arteries in the vascular flow maps produced by LSI. We apply this combined technique to mouse cerebral vascular network in vivo, comparing imaging through the skull, to the dura mater and brain directly through a craniectomy, and through a transparent cranial "Window to the Brain" (WttB) implant. Study Design/Materials and Methods: The WttB implant used in this study is made of a nanocrystalline Yttria‐Stabilized‐Zirconia ceramic. MSRI was conducted using white‐light illumination and filtering the reflected light for 560, 570, 580, 590, 600, and 610 nm. LSI was conducted using an 810 nm continuous wave near‐infrared laser with incident power of 100 mW, and the reflected speckle pattern was captured by a complementary metal‐oxide‐semiconductor (CMOS) camera. Results: Seven vessel branches were analyzed and comparison was made between imaging through the skull, craniectomy, and WttB implant. Through the skull, MSRI did not detect any vessels, and LSI could not image microvessels. Imaging through the WttB implant, MSRI was able to identify veins versus arteries, and LSI was able to image microvessels with only slightly higher signal‐to‐noise ratio and lower sharpness than imaging the brain through a craniectomy. Conclusions: This study demonstrates the ability to perform MSRI‐LSI across a transparent cranial implant, to allow for cerebral vascular networks to be mapped, including microvessels. These images contain additional information such as vein‐artery separation and relative blood flow velocities, information which is of value scientifically and medically. The WttB implant provides substantial improvements over imaging through the murine cranial bone, where microvessels are not visible and MSRI cannot be performed. Lasers Surg. Med. © 2019 Wiley Periodicals, Inc.